The electronics revolution : inventing the future - Williams, J. B. (Springer, 2017)
This book is about how electronics, computing, and telecommunications have profoundly changed our lives - the way we work, live, and play. It covers a myriad of topics from the invention of the fundamental devices, and integrated circuits, through radio and television, to computers, mobile telephones and GPS. Today our lives are ruled by electronics as they control the home and computers dominate the workspace. We walk around with mobile phones and communicate by email. Electronics didn't exist until into the twentieth century. The industrial revolution is the term usually applied to the coming of steam, railways and the factory system. In the twentieth century, it is electronics that has changed the way we gather our information, entertain ourselves, communicate and work. This book demonstrates that this is, in fact, another revolution.
Keywords: Electronics -- Technological innovations.; elektronické knihy; electronic books